Development of MUSI board media (multi-functional) with index card match learning model of LCM GCD material - Yuniar Ika Putri Pranyata; Eka Sasmita Sari; Trija Fayeldi; Darius Seow (Jurnal Pendidikan Matematika (JPM), 2026)
Learning about Least Common Multiple (LCM) and Greatest Common Divisor (GCD) in junior high school still faces challenges because students often struggle to understand the concepts of multiples and factors through conventional instruction. Previous studies have developed MUSI Board media, but its integration with a structured active learning model, such as Index Card Match, remains limited, particularly at the junior high school level. This study aimed to develop MUSI Board learning media integrated with the Index Card Match model for LCM and GCD material that is valid, practical, and effective. This research used the ADDIE development model, consisting of analysis, design, development, implementation, and evaluation. The subjects were 9 students in a limited trial and 20 students in a large-scale trial at SMPN 17 Malang. Data were collected through expert validation sheets, student response questionnaires, and learning outcome tests. The results showed that the MUSI Board obtained validity scores of 96.4% from media experts, 93.75% from material experts, and 90.63% from practitioners, all categorized as very valid. The practicality scores were 97.57% in the limited trial and 92.18% in the large-scale trial, both categorized as very practical. The effectiveness score reached 93.5%, indicating that the media was very effective in supporting student learning outcomes. These findings imply that the MUSI Board integrated with Index Card Match can be used as an alternative active learning medium for number material in junior high school.